1996
DOI: 10.1590/s1516-31801996000200007
|View full text |Cite
|
Sign up to set email alerts
|

Direct immunofluorescence in Lupus Erythematosus (LE)

Abstract: One hundred and twenty-six patients with LE were studied. They were distributed as follows: 84 with DLE, 13 with SALE and 29 with SLE. Biopsies from the skin lesions were performed and submitted to DIF. Positive results were equal to 69, 61.5 and 72.4 percent of the DLE, SALE and SLE cases, respectively. These data are in accordance with the literature. IgM was the most frequently found immunoglobulin, followed by the association IgM + C3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Our previous research showed that the detection rate of immunoreactants in lesional skin varied from 30% to 50% and that IgM was the most frequent immunoreactant [12], which is consistent with other published data [3], [13][15]. We enrolled 64 patients diagnosed with SLE and examined DIF conducted on lesional skin to assess whether the type and number of cutaneous immunoreactants present in the lesional skin correlated with serological disorders and disease severity as measured by the SLEDAI.…”
Section: Introductionsupporting
confidence: 85%
“…Our previous research showed that the detection rate of immunoreactants in lesional skin varied from 30% to 50% and that IgM was the most frequent immunoreactant [12], which is consistent with other published data [3], [13][15]. We enrolled 64 patients diagnosed with SLE and examined DIF conducted on lesional skin to assess whether the type and number of cutaneous immunoreactants present in the lesional skin correlated with serological disorders and disease severity as measured by the SLEDAI.…”
Section: Introductionsupporting
confidence: 85%
“…The diagnosis of KFD was performed by lymph node biopsy, but some discrepancies with this diagnosis were seen from serologic parameters such as positive antinuclear antibody, dsDNA, extractable nuclear antigen, SSA/Ro, and anti‐straight muscle antibodies.. The DIF showed the association of IgM+ C3 microgranular deposits at the epidermal–dermal junction (in accordance with the literature), typical DIF of lupus erythematosus and cutaneous lupus erythematosus 10 …”
Section: Discussionsupporting
confidence: 68%
“…Our patient reported an episode of malar rash and erythema at the age of 20 years old, then three years ago she developed a lupus-like panniculitis and itchy (a) (b) Figure 1 Erythematous scleroatrophic skin lesions first appeared on the superior, external part of the arms, and on the buttock the association of IgM+ C3 microgranular deposits at the epidermal-dermal junction (in accordance with the literature), typical DIF of lupus erythematosus and cutaneous lupus erythematosus. 10 As the diagnosis of KFD is mainly based on histopathological studies of the affected lymph nodes (to better define the patient's skin lesions), we performed an immunohistochemical and EM study on lesional skin.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The second most common deposit at the DEJ was IgM, which tended to exhibit a strong intensity in association with LE. [15][16][17] Considering all the results, we suggest that any immunoreactant deposit at CB plus fibrinogen deposition, whether alone or combined with other immunoreactants at DEJ, favors LP. Meanwhile, the deposition of any immunoreactant at CB plus IgG or intense IgM at DEJ, favors LE.…”
Section: Discussionmentioning
confidence: 75%